1995
DOI: 10.1006/obhd.1995.1026
|View full text |Cite
|
Sign up to set email alerts
|

Probability Models for Duration: The Data Don′t Tell the Whole Story

Abstract: Probability models for duration have been applied to a wide range of individual-level and organizational phenomena. Seemingly similar models may, however, produce different results. Building on previous work by Morrison & Schmittlein (1980) and Schmittlein and Morrison (1983), we propose a hierarchy of models and show how an analysis of the results across models helps explain why different studies came to different conclusions. This analysis also leads to substantive insights that even the most complete model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…step-wise, period-by-period approximation), the estimated variance for the mixing distribution (capturing the extent of heterogeneity) most often converges to zero. For example, Vanhuele, Dekimpe, Sharma, and Morrison (1995) found that the estimated variance for the mixing distribution, which captures the heterogeneity in the hazard-rate model, becomes small when they include time dummy variables and all the available covariates.…”
Section: Discussion and Implications For Marketing Modelers And Managmentioning
confidence: 98%
“…step-wise, period-by-period approximation), the estimated variance for the mixing distribution (capturing the extent of heterogeneity) most often converges to zero. For example, Vanhuele, Dekimpe, Sharma, and Morrison (1995) found that the estimated variance for the mixing distribution, which captures the heterogeneity in the hazard-rate model, becomes small when they include time dummy variables and all the available covariates.…”
Section: Discussion and Implications For Marketing Modelers And Managmentioning
confidence: 98%
“…Given our definitions, each model will use only one rise observation and one fall observation for each athlete. In addition, many previous empirical studies (Gupta, 1991;Han & Hausman, 1990;Meyer, 1990;Vanhuele, Dekimpe, Sharma, & Morrison, 1995) have shown that not accounting for unobserved heterogeneity has more of an impact on the estimation of the time dependence (baseline hazard) than on the estimates of the covariates. Given our focus on the latter, we feel that not accounting for unobserved heterogeneity will not be too influential.…”
Section: Defining Points Of Rise and Fallmentioning
confidence: 97%
“…To incorporate covariates into the model, we first propose an expression for the hazard function, and subsequently use a general relationship between a distribution's hazard and survivor functions. Following Vanhuele et al (1995), we write the hazard function…”
Section: Modeling the Timing Of Relapsementioning
confidence: 99%
“…To estimate the parameters of interest (l 0 , and an t b uc), expression for the survival function associated with the hazard function in Equation 2is needed. When the timevarying covariates are assumed to remain constant within a given month but are allowed to vary from month to month, it can be shown that (Vanhuele et al 1995) 0l…”
Section: Modeling the Timing Of Relapsementioning
confidence: 99%
See 1 more Smart Citation